Assessing Chinese Employee Job Preferences and Employee Retention Strategies: The Case of a Strategic Alliance of Foreign Multinational in China - MA, XU (2008)
According to the popularity of "job hoping" in current Chinese labour market, it is essential for multinationals, particularly for multinational strategic alliances (MSAs), to be aware of their employees' job preferences in order to design effective retention strategies. This study discloses many differences and similarities in job preferences between Chinese overseas graduates and domestic graduates. Foreign educated graduates were more interested in job-related factors, such as "advancement" and "type of work"; whereas Chinese domestic graduates thought "benefits" and "work conditions" were important. "Pay" was considered as the most important attribute by both parties. The pattern of preferences in current young Chinese employees was distinct from U.S. employees, but not as much as before. Because both Chinese and U.S. employees emphasised on "advancement" and "type of work". The preferences in current young Chinese employees also changed a lot comparing with the past. Chinese people's job preferences shifted from economic benefits to job itself. Reasons of these marked changes are the cultural shocks and national developments.